Heavy metals and proximate analysis of Sihar (Rhazya stricta Decne) collected from different sites of Warcha salt mine, Salt Range, Pakistan - Khan, Zafar Iqbal; Ahmad, Kafeel; Bibi, Hafiza Farhat; Ahmad, Iftikhar; Muhammad, Fatima Ghulam; Ashfaq, Asma; Ejaz, Abid; Sameen, Asifa; Nadeem, Muhammad; Ugulu, Ilker (International Journal of Applied and Experimental Biology, 2023)
Rhazya stricta is an important medicinal plant species distributed all over the Warcha salt mine in Pakistan. Analysis of proximate composition and metals is a commendable job to assess the suitability of the exploitation of medicinal plants on a large scale by ethnic communities. The proximate analyses (moisture, fiber, ash, crude fats, proteins and carbohydrates) of all the samples collected from five different sites (Table 1) were carried out. Moreover, different inorganic elements in the samples were also determined. The maximum and the minimum moisture content in Rhazya stricta was observed at Site 4 (31.21%) and Site 2 (29.14%), respectively. The maximum and the minimum ash concentrations were recorded in the populations collected from Site 2 (7.48%) and Site 5 (6.25%), respectively. The maximum fat content was found in the Site 3 (3.91%) population, whereas the minimum contents of crude fiber were observed in the population from Site 2 (12.2%). The maximum concentration of crude protein was observed in the plants from Site 5 (9.93%), whereas the minimum contents of carbohydrates were observed in the plants from Site 2 (48.4%). Essential and nonessential elements like potassium (K), magnesium (Mg), iron (Fe), nickel (Ni), chromium (Cr), cadmium (Cd), cobalt (Co), copper (Cu), manganese (Mn), and zinc (Zn) were analyzed in the roots, stem and leaves of Rhazya stricta. The maximum K content (6836.886 mg/kg) was found in the roots of plants collected from Site 5 and the minimum in the leaves (5528.795 mg/kg) collected from Site 3. The highest concentration of magnesium was found in the roots of plants from Site 3 (2414.46 mg/kg), whereas the lowest concentration of iron was recorded in the leaves of Site 4 (31.45 mg/kg) plants. The maximum and the minimum concentrations of cobalt were detected in the roots of plants from Site 1 (0.320 mg/kg) and in the leaves of plants from Site 4 (0.135 mg/kg), respectively. The minimum concentration of leaf cadmium was recorded in plant population from Site 4, whereas in the same population the maximum level of root nickel was recorded. The highest concentration of copper was observed in the stem of plant population from Site 2 (0.297 mg/kg). The concentrations of most of the elements appraised in the present study are well below the overall permissible limits of these elements in medicinal plants determined by WHO, so this plant from the Warcha mine can be utilized without harm by herbal practitioners and pharmaceutical industry.